Cooperative parent mediated therapy for Italian children with autism spectrum disorder: a clinical experimental study in a community healthcare service in Italy - Alessandra Carta; Laura Casula; Salvatorica Manca; Mariangela Valentina Puci; Giuseppina Puseddu; Giuseppina Puseddu; Elisa Fucà; Giovanni Sotgiu; Stefano Vicari; Stefano Vicari; Stefano Sotgiu; Giovanni Valeri (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionThis Clinical Experimental Study aimed to evaluate the effectiveness of Cooperative Parent Mediated therapy (CPMT), a targeted parent-coaching program for Autism Spectrum Disorder (ASD), in Community Healthcare Service in Italy.MethodsForty children with ASD and their parents were randomly assigned to treatment conditions: the Control group received Individual Treatment As Usual (TAU Control group); while CPMT group received weekly parent–child sessions in addition to Individual TAU. Primary blinded outcomes were 6-months post-intervention change in parent–child interaction scores. Secondary outcomes included ASD symptom severity, adaptive functioning and parental stress levels. Baseline and post-treatment evaluations, at 6 months of follow up, were performed by an independent team.ResultsCPMT group showed significant add-on benefits on parent-child interactions, severity of autism symptoms, adaptive skills and parental stress level.DiscussionThis study provides preliminary evidence for the effectiveness of the CPMT model also in community services, representing a further step forward in research on the implementation of therapy for ASD in community healthcare service.